Antimicrobial activity of linear lipopeptides derived from BP100 towards plant pathogens - Oliveras, Àngel (PLoS One, 2018)
A collection of 36 lipopeptides were designed from the cecropin A-melittin hybrid peptide BP100 (H-Lys-Lys-Leu-Phe-Lys-Lys-Ile-Leu-Lys-Tyr-Leu-NH(2)) previously described with activity against phytopathogenic bacteria. These lipopeptides were synthesized on solid-phase and screened for their antimicrobial activity, toxicity and proteolytic stability. They incorporated a butanoyl, a hexanoyl or a lauroyl group at the N-terminus or at the side chain of a lysine residue placed at each position of the sequence. Their antimicrobial activity and hemolysis depended on the fatty acid length and its position. In particular, lipopeptides containing a butanoyl or a hexanoyl chain exhibited the best biological activity profile. In addition, we observed that the incorporation of the acyl group did not induce the overexpression of defense-related genes in tomato. Best lipopeptides were BP370, BP378, BP381, BP387 and BP389, which were highly active against all the pathogens tested (minimum inhibitory concentration of 0.8 to 12.5 μM), low hemolytic, low phytotoxic and significantly stable to protease degradation. This family of lipopeptides might be promising functional peptides useful for plant protection.